E-047 Navigation of a Flow-Diverting Stent across the Neck of a Giant Supraclinoid Internal Carotid Artery Aneurysm with a Balloon Anchor Technique. (26th July 2014) - Ding, D; Starke, R; Evans, A; Jensen, M; Liu, K
Abstract : Introduction: Flow-diverting stents (FDS), such as the Pipeline Embolization Device (PED) have drastically altered the therapeutic strategies for giant intracranial aneurysms. Gaining endovascular access with a microcatheter to the portion of the parent artery distal to the aneurysm neck is requisite for safe and effective stent deployment. Giant aneurysms are often associated with vascular tortuosity which necessitates significant catheter support systems to allow the manoeuvring of PEDs across the aneurysm neck. Methods: We present a case of a giant supraclinoid internal carotid artery aneurysm (ICA) which was successfully treated with a FDS utilising a balloon anchor technique to facilitate direct microcatheter access across the aneurysm neck. Results: A 59 year-old female presented with a giant (2.9 cm in maximal diameter) supraclinoid ICA aneurysm arising from the branch point of the superior hypophyseal artery (SHA) extending into the sella turcica. Given the size and location of the aneurysm, the decision was made to treat the patient by an endovascular approach using a PED. A ReFlex 058 guide catheter was navigated into the left ICA through a Flexor Shuttle 087 guiding sheath so that control angiograms could be performed throughout the stent procedure. Initially a Marksman microcatheter (ev3) was advanced past the aneurysm into the left middle cerebral artery (MCA) trunk. The PED was advanced through the Marksman microcatheter, but catheter herniation into the aneurysm, caused by the course of blood flow through the giant aneurysm sac, precluded effective stent placement and delivery of the stent past the aneurysm neck. Therefore the Marksman microcatheter and PED were removed and the decision was made to use a balloon anchor technique to improve endovascular access across the aneurysm neck. Next, a Sceptre C balloon, placed within a DAC 044 catheter, was advanced over a Transend 014 microguidewire to the left SHA aneurysm. Under continuous fluoroscopic guidance, the Sceptre C balloon was advanced into the left MCA and inflated. With the balloon serving as an anchor, the DAC 044 catheter was advanced through the aneurysm into the supraclinoid ICA. There was a significant amount of catheter redundancy within the aneurysm sac. By slowly pulling down the DAC 044 catheter, the length of redundant catheter within the aneurysm sac gradually decreased until the catheter was only traversing the aneurysm neck. The Sceptre C balloon was then deflated and removed from the patient. Next, an Excelsior XT-27 microcatheter was advanced through the DAC 044 into the supraclinoid ICA distal to the aneurysm neck. A 5.0 × 30 mm PED was then advanced through the XT-27 microcatheter and deployed across the aneurysm neck in a standard fashion. The patient was discharged home two days after the endovascular procedure without neurological deficits. Conclusions: Direct microcatheter access across the neck of an aneurysm is a critical step prior to deployment of a FDS. A balloon anchor technique may be used to safely achieve a direct and effective microcatheter position across the neck of a giant aneurysm to allow FDS treatment of these lesions. Disclosures: D. Ding: None. R. Starke: None. A. Evans: None. M. Jensen: None. K. Liu: None.